Innovative development of technoparks as a key to the recovery and sustainable development of Ukraine. (Economics and region, 2022)
The development of innovative activities of technology parks and their investment support is one of the strategically important tasks for Ukraine today. The statistical data on the dynamics of innovation-active business development are investigated. The financing of innovation activities by both domestic investors, the state and foreign partners during the COVID-19 crisis and in war conditions is analyzed. The data on the projects of existing technology parks and planned industrial, scientific and environmental technology parks with the prospect of benefiting from their effective functioning in Ukraine are summarized. Particular attention is paid to the detailed acquaintance with interesting investment projects of 2020-2022, as well as the study of investment attractiveness during the Russian-Ukrainian war. The prospects for the development of technology parks and innovations for our country after the war are highlighted.
Keywords: innovations; technoparks; industrial parks; science parks; eco-technoparks; financing; investments